Effect of Germination on Bioactive Compounds and Antioxidant Properties of Riceberry Rice for Functional Ice Cream - Srisukong, Amornrat; Pinkaew, Panyapathk; Pichaiyongvongdee, Suwanna; Nukit, Natchanok; Yuyen, Yutthaya; Itsarasook, Khwunjit; Burakorn, Jiraporn (Journal of Food Health and Bioenvironmental Science, 2025)
This study investigates the effects of germination time on the bioactive compounds, chemical composition, and antioxidant properties of Riceberry rice, along with the incorporation of germinated Riceberry milk (GRM) into ice cream. Germination significantly increased gamma-aminobutyric acid (GABA) levels, reaching a peak at 20 h (19.49 mg/100 g dry basis), while total phenolic content (TPC) and antioxidant capacity (DPPH assay) showed a slight decline after 18 h. At 20 h, germinated rice exhibited lower carbohydrate content and higher levels of fat, fiber, and ash compared to non-germinated rice. GRM, containing 1.74% protein, 1.10% fat, and an antioxidant capacity of 172.06 mmol Trolox/100 g, was incorporated into ice cream formulations at concentrations ranging from 0% to 50%. Increasing GRM content improved the ice cream’s antioxidant capacity and TPC, with the highest levels observed at 50% GRM (14.47 mg gallic acid/100 g and 31.33 mmol Trolox/100 g, respectively). GRM addition also affected physical attributes such as apparent viscosity and overrun. Sensory evaluation revealed that high GRM concentrations (≥30%) negatively impacted texture, taste, and overall acceptability. In contrast, the 20% GRM formulation provided a favorable balance between enhanced nutritional properties and consumer acceptance, showing no significant difference from the control. These findings support the potential of GRM as a functional ingredient in health-oriented frozen desserts, offering nutritional and antioxidant benefits without compromising sensory quality when used at optimal levels.